Analisis Potensi Pencemaran Air Sungai Di Lingkungan Hutan Tropis Lembap Kalimantan Timur Menggunakan Model Regresi Weibull - Desty, Yola; Suyitno, Suyitno; Purnamasari, Ika (Program Studi Statistika FMIPA Universitas Mulawarman, 2025)
Weibull Regression Model (WR) is the Weibull distribution in which scale parameter is stated in the regression parameter. WR model derived from the interrelated functions of Weibull Distribution, consisting of Weibull survival regression model, Weibull cumulative distribution regression model, Weibull hazard regression model, and Weibull mean regression. The purpose of this study was to obtain the pollution potential information of river water in east Kalimantan and to obtain the factors that influence it through RW modeling on dissolved oxygen (DO) data in 2022. Research data is secondary data provided by life inveronment of East Kalimantan Province. The parameter estimation method is maximum likelihood estimation (MLE). The study concluded the pollution potential information of river water in east Kalimantan Timur based on modeling RW DO data consists of the chance the unpolluted river water is 0.6868, chance of polluted river water is 0.3132, the water pollution rate is 0.4349 locations/ ppm, and average river water DO is 5.6003 ppm. Factors that influence the pollution potential of river water is nitrite concentration, water temperature, and degree of water color.